The European citizens' initiative within democracy context - Campina, Ana (2017)
Human Rights, Democracy, and the Rule of Law are the main European values that supported the construction of the European Union (EU). The European citizenship initiative is a right that was introduced by the Lisbon Treaty as a new instrument for participative transnational democracy.